2019
DOI: 10.1152/ajpheart.00303.2019
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide regulation of renal and mesenteric blood flow

Abstract: Hydrogen sulfide (H2S) dilates isolated arteries, and knockout of the H2S-synthesizing enzyme cystathionine γ-lyase (CSE) increases blood pressure. However, the contributions of endogenously produced H2S to blood flow regulation in specific vascular beds are unknown. Published studies in isolated arteries show that CSE production of H2S influences vascular tone more in small mesenteric arteries than in renal arteries or the aorta. Therefore, the goal of this study was to evaluate H2S regulation of blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
(70 reference statements)
1
4
0
Order By: Relevance
“…In the present study, we showed that resistance mesenteric arteries express all three H 2 S-producing enzymes, CSE being the most abundant, with a minor expression of both CBS and 3MPST, in agreement with previous reports [ 38 ] and confirming the relevant physiological role of CSE in the control of mesenteric blood flow [ 37 , 39 ]. Although CSE and 3MPST play major roles in the cardiovascular system (they are also the main enzymes expressed in vessels such as the coronary artery [ 40 ] and aorta [ 41 ]), some studies performed on human endothelial cells from an umbilical vein (HUVEC) point out that CBS activity can be involved in endothelial function regulation [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we showed that resistance mesenteric arteries express all three H 2 S-producing enzymes, CSE being the most abundant, with a minor expression of both CBS and 3MPST, in agreement with previous reports [ 38 ] and confirming the relevant physiological role of CSE in the control of mesenteric blood flow [ 37 , 39 ]. Although CSE and 3MPST play major roles in the cardiovascular system (they are also the main enzymes expressed in vessels such as the coronary artery [ 40 ] and aorta [ 41 ]), some studies performed on human endothelial cells from an umbilical vein (HUVEC) point out that CBS activity can be involved in endothelial function regulation [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…Resistance arteries are the main vessels responsible for the control of blood flow, and consequently blood pressure, due to their small internal diameter and the thick muscular wall in relation to the narrow lumen [ 8 , 37 ]. In this way, investigations on the vascular effects of new compounds on resistance vessels are a mandatory step for the development of novel cardiovascular drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, renal blood flow can be increased by intrarenal arterial infusion of NaHS [ 52 ]. Additionally, a CSE inhibitor decreased blood flow in the renal artery in rats, suggesting CSE-derived H 2 S has a prominent role in regulating renal blood flow and vascular resistance in renal circulation [ 53 ].…”
Section: Hydrogen Sulfide In Kidney Health and Diseasementioning
confidence: 99%
“…Treatment with a phosphorothioate-based synthetic H 2 S donor JK-1 suppresses the activation of RAAS, reduces BP, and improves renal functions (Li et al, 2018). It has also been shown that the treatment of anesthetized rat models with H 2 S donor Na 2 S can significantly decrease the BP and mesenteric resistance; meanwhile, the administration of CSE inhibitors (β-cyanoalanine) and PAG could increase BP and resistance in both mesenteric and renal circulations (Morales-Loredo et al, 2019). Another component involved in BP regulation is cyclic guanosine monophosphate (cGMP).…”
Section: Blood Pressure Regulationmentioning
confidence: 99%
“…Although primary injuries can be well repaired, the defects in the repair mechanism can augment the condition, thus resulting in tissue and organ injury. For instance, HIF activation can prevent the degeneration of tissue by improving oxygen balance and promoting cell repair ( Bernhardt et al, 2006 ); however, its prolonged stimulation can result in the progression of tissue injury by increasing ECM accumulation and inflammatory responses ( Haase, 2012 ; Conde et al, 2017 ). The injuries are the result of high apoptosis, podocyte loss, accumulation of ECM, and inflammation.…”
Section: The Mechanism Of Action Of Hydrogen Sulfide In Common Kidneymentioning
confidence: 99%